Integrated complex care coordination for children with medical complexity: A mixed-methods evaluation of tertiary care-community collaboration - Cohen Eyal; Lacombe-Duncan Ashley; Spalding Karen; MacInnis Jennifer; Nicholas David; Narayanan Unni G; Gordon Michelle; Margolis Ivor; Friedman Jeremy N (BMC, 2012)
Abstract Background Primary care medical homes may improve health outcomes for children with special healthcare needs (CSHCN), by improving care coordination. However, community-based primary care practices may be challenged to deliver comprehensive care coordination to complex subsets of CSHCN such as children with medical complexity (CMC). Linking a tertiary care center with the community may achieve cost effective and high quality care for CMC. The objective of this study was to evaluate the outcomes of community-based complex care clinics integrated with a tertiary care center. Methods A before- and after-intervention study design with mixed (quantitative/qualitative) methods was utilized. Clinics at two community hospitals distant from tertiary care were staffed by local community pediatricians with the tertiary care center nurse practitioner and linked with primary care providers. Eighty-one children with underlying chronic conditions, fragility, requirement for high intensity care and/or technology assistance, and involvement of multiple providers participated. Main outcome measures included health care utilization and expenditures, parent reports of parent- and child-quality of life [QOL (SF-36®, CPCHILD©, PedsQL™)], and family-centered care (MPOC-20®). Comparisons were made in equal (up to 1 year) pre- and post-periods supplemented by qualitative perspectives of families and pediatricians. Results Total health care system costs decreased from median (IQR) $244 (981) per patient per month (PPPM) pre-enrolment to $131 (355) PPPM post-enrolment (p=.007), driven primarily by fewer inpatient days in the tertiary care center (p=.006). Parents reported decreased out of pocket expenses (p<.0001). Parental QOL did not significantly change over the course of the study. Child QOL improved between baseline and 6 months in two PedsQL™ domains [Social (p=.01); Emotional (p=.003)], and between baseline and 1 year in two CPCHILD© domains [Health Standardization Section (p=.04); Comfort and Emotions (p=.03)], while total CPCHILD© score decreased between baseline and 1 year (p=.003). Parents and providers reported the ability to receive care close to home as a key benefit. Conclusions Complex care can be provided in community-based settings with less direct tertiary care involvement through an integrated clinic. Improvements in health care utilization and family-centeredness of care can be achieved despite minimal changes in parental perceptions of child health.